EFFECTIVENESS OF MYCORRHIZAE AND SP-36 FERTILIZER APPLICATION ON GROWTH AND YIELD OF SORGHUM (Sorghum bicolor (L) moench) - Saddam Purwandi; Sri Susanti Ningsih; Rita Mawarni (Universitas Asahan, 2018)
This research was conducted in Tanjung Alam Village, Sei Dadap Subdistrict, Asahan Regency, North Sumatera Province with flat topography with height of place ± 20 m above sea level. The study was conducted on 9th February 2018 to 17th April 2018. The materials used in this research are sorghum seeds of kawali varieties, mycorrhiza, SP-36 fertilizer, matador 25 EC insecticide (active ingredient Lamda Sihalotrin), Dithane M-45 Fungicide (Mankozed active ingredient). The tools used in this research are hoe, watering can, handsprayer, treatment plate, replica plate, banner, plastic strap, meter, stationery, calculator and scales. This research was arranged based on Factorial Randomized Block Design (RBD) with 2 treatment factors and 4 replications. The first factoris the dosage of mycorrhiza with 2 levelsie: M0 = 0 g/plot, M1 = 15 g / plot. The second factor was the application of SP-36 fertilizer, with 3 levelsie S1 = 250 g/plot, S2 = 187.75 g/plot, and S3 = 125 g/plot. The results of dosage of mycorrhizal dosage showed significant effect on the growth of sorghum on the observation parameter of leaf number 8 weeks after planting, with the best treatment at dose 0 g/plot). Application of SP-36 fertilizer showed no significant effect on all observation parameters. The interaction between the application of mycorrhizal dose and SP- 36 fertilizer to the growth and production of sorghum showed no significant effect on all observation parameters.